Lung cancer and arsenic exposure in drinking water: a case-control study in northern Chile - Ferreccio Catterina; Psych Claudia Gonzalez; Stat Vivian Milosavjlevic; Gredis Guillermo Marshall; Sancha Ana María (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
In some Chilean cities, levels of arsenic (As) in drinking water reached 800 µg/L between 1950 and 1970, while current levels are 40 µg/L. To evaluate the causal role of this exposure in lung and bladder cancers, we conducted a case-control study in Regions I, II, and III of the country. From 1994 to 1996, cases diagnosed as lung cancer and two hospital controls were entered in the study; one control was a patient with a cancer, while the other was a patient without cancer, both conditions unrelated to As. Controls were matched with cases by age and sex. A standard survey containing questions about residence, employment, health history, was administered to study subjects. Data on As concentrations in water were obtained from records of the municipal water companies. A total of 151 lung cancer cases and 419 controls (167 with cancer and 242 without cancer) were enrolled. Median level of lifetime As exposure was significantly higher among cases, with a clear dose-response relationship between mean As exposure levels, with an OR (95% CI) of: 1, 1.7 (0.5-5.1), 3.9 (1.2-13.4), 5.5 (2.2-13.5), and 9.0 (3.6-22) for strata one to five respectively. This study provides new evidence that As in drinking water can cause internal cancers and gives an estimate of the form of this relationship.